(untitled) (Journal of the College of Basic Education, 2022)
What was the instinct and ancient traditions that marked the Arab taste in its character and that settled inThe unconscious in the writer’s soul, this study came to address the frameworks that show the impact of the environment on the poet’s languageShe had a prominent role in the construction of the Arabic poem, especially with regard to the words of the poem, and what it carriesMeanings and similes, and this environment is the nature that represented the geographical location and its characterUrban. There is no doubt that the environment has a great impact on building the personality of the creative writer, with what surrounds himA Bedouin or a person who influences and is affected by his environment according to the elements and tools that this environment contains, and their influence is on the poetIn presenting his poems, and choosing the appropriate tools for formulating them, every environment contains tools and wordsIt differs from the other environment as the urban poet depicts the urban features that surround him.